ANALISIS NILAI TAMBAH PENGOLAHAN DAN KELAYAKAN FINANSIAL MINUMAN BUBUK HERBAL BAWANG BERLIAN (Eleutherine americana Merr) - Hertika Dewi, Ni Putu; Satriawan, I Ketut; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 2 (2017): April, 2017)
The purpose of the study is to determine the value added processing and calculate the feasibility of the business of herbal drink diamond powder (Eleutherine Americana Merr). Value added analysis using Hayami method and Financial Feasibility Analysis uses quantitative descriptive analysis using calculations profit and loss, Net Present Value (NPV), Internal Rate of Return (IRR), Net B/C Ratio, Payback Period (PP), and Break Event Point (BEP). The results showed that added value obtained from the processing of diamond onion is Rp. 166.955 / Kg. The business of herbal drink powdered diamond as a whole is profitable with a net profit of Rp. 200.085.601 of year and worth developing. It is based on financial feasibility analysis that is Net Present Value (NPV) of Rp. 391.505.116, Internal Rate of Return (IRR) of 30%, Payback Period (PP) for 1 year 4 months, and Net B / C Ratio of 2,14. Sensitivity analysis indicates that an increase in operational cost of 10% and a 10% revenue decrease does not affect the feasibility of the project. Based on the results of research on the business of herbal drink powder diamond is very feasible to be developed. Keywords: diamond onion, value added, financial feasibility